Environmental sustainability and human well-being indicators from the ecosystem perspective in the Middle Paraíba Region, Rio de Janeiro State, Brazil Indicadores de sustentabilidade ambiental e de bem-estar em perspectiva ecossistêmica na Região do Médio Paraíba, Rio de Janeiro, Brasil - Carlos Machado de Freitas; Gabriel Eduardo Schütz; Simone Gomes de Oliveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
Population urbanization is a global trend, and socioeconomic activities in urban areas cause changes that affect the environment and human well-being beyond the specific territories, thus connecting urban to non-urban areas and creating city-regions. This article's objective, from an ecosystem perspective, is to gather a set of information on municipalities (counties) belonging to the Middle Paraíba River Valley Region in the State of Rio de Janeiro, Brazil, in order to identify conditions and trends in environmental sustainability and well-being. The conceptual framework adopted here was that of the Millennium Ecosystem Assessment, identifying direct and indirect driving forces that affect human well-being, with health as a component of the latter. We used a set of available public-domain data and information sources on the municipalities, grouped by socioeconomic and environmental conditions and the soundness of institutional structural well-being for sustainability. The indicators used here point to a process of degradation in the ecosystem services that has still not been prevented by the prevailing institutional structure, thus increasing constraints on well-being and the spread of socio-environmental impacts in the middle and long terms. A urbanização da população é uma tendência mundial e as atividades sócio-econômicas nestas áreas resultam em alterações que afetam o meio ambiente e o bem-estar humano para além de seus territórios, conectando áreas urbanas com não-urbanas, constituindo cidades-regiões. O objetivo deste artigo é, em perspectiva ecossistêmica, reunir um conjunto de informações sobre municípios integrantes da Região do Médio Paraíba, Estado do Rio de Janeiro, Brasil, de modo a indicar condições e tendências da sustentabilidade ambiental e do bem-estar. A estrutura conceitual adotada teve como referência a adotada no Millennium Ecosystem Assessment, identificando forças motrizes diretas e indiretas que afetam o bem-estar humano, sendo a saúde um componente do mesmo. Utilizou-se um conjunto de fontes de dados e informações sobre os municípios disponíveis e de acesso público agrupadas em condições sócio-econômicas, ambientais e de bem-estar estrutural institucional para a sustentabilidade. Os indicadores utilizados apontam para um processo de degradação dos serviços dos ecossistemas que ainda não encontram barreiras suficientes na estrutura institucional vigente, potencializando restrições ao bem-estar e ampliação dos impactos sócio-ambientais no médio e longo prazos.